2016
DOI: 10.1515/pjvs-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation of apoptosis and proliferation in the mucous membrane of selected uterine regions in pre-pubertal bitches exposed to low doses of zearalenone

Abstract: Mycotoxins are toxic secondary metabolites produced by fungi. Those biologically active compounds occur naturally and they include zearalenone (ZEN), a mycotoxin that contaminates plant material, including the ingredients used in the production of commercial dog food. The influence of monotonic, low-dose and long-term exposure to ZEN on pre-pubertal bitches has not been fully explored to date. This paper describes a 42-day experiment performed on clinically healthy female dogs aged approximately 70 days, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…During the synthesis of these catechol metabolites, ZEN activity becomes similar to that of endogenous estrogens E 2 and E 1 . These promiscuous steroids [ 40 ] and steroid-like substances are associated with the risk of bowel cancer [ 41 ], breast cancer [ 35 ], uterine cancer [ 9 ], and malignant changes in other estrogen-sensitive organs [ 21 ]. There is evidence to indicate that E 2 /E 1 catechol metabolites are weak genotoxins that contribute to malignant transformations by producing quinones that generate DNA adducts [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the synthesis of these catechol metabolites, ZEN activity becomes similar to that of endogenous estrogens E 2 and E 1 . These promiscuous steroids [ 40 ] and steroid-like substances are associated with the risk of bowel cancer [ 41 ], breast cancer [ 35 ], uterine cancer [ 9 ], and malignant changes in other estrogen-sensitive organs [ 21 ]. There is evidence to indicate that E 2 /E 1 catechol metabolites are weak genotoxins that contribute to malignant transformations by producing quinones that generate DNA adducts [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The above is confirmed by the hormesis paradigm [ 6 , 7 ]. Doses below the lowest observed adverse effect level (LOAEL) values [ 8 , 9 ] that produce subclinical symptoms of disease are referred to as no observed adverse effect levels (NOAEL) doses [ 10 ]. The lowest measurable dose that enters positive interactions with the host’s body in various stages of life is known as the minimal anticipated biological effect level (MABEL) dose [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…ZEA is structurally similar to estrogen and competes with estradiol for binding to estrogen receptors, and stimulates estrogenic activity, which may cause several physiological alterations in the reproductive tract (56). In vitro study has indicated that ZEA may regulate metabolic processes, including cell proliferation, differentiation and apoptosis (57). The regulatory role of ZEA in endometriosis has also been demonstrated (58).…”
Section: Discussionmentioning
confidence: 99%
“…The health (toxicological) effects of low mycotoxin doses became apparent in the last decade. They are associated with hormesis [ 36 , 37 ], a biological phenomenon whereby exposure to doses below the NOAEL [ 38 ] induces disease without clinical symptoms (subclinical state) [ 15 , 39 ] or delivers beneficial effects for the host in various stages of life [ 40 ]. The dose-response relationship was put into question by the low-dose hypothesis, in particular with regard to hormonally active chemicals [ 41 ] such as ZEN and its metabolites.…”
Section: Introductionmentioning
confidence: 99%